A MEMS grating modulator with a tunable sinusoidal grating for large-scale extendable apertures - Datai Hui; Dongpeng Li; Binbin Wang; Yongqian Li; Jiaqian Ding; Laixian Zhang; Dayong Qiao (Microsystems & Nanoengineering)
Abstract Microelectromechanical system (MEMS) grating modulators enable versatile beam steering functions through the electrostatic actuation of movable ribbons. These modulators operate at ultrahigh frequencies in the hundred kHz range, and their micromirror-free configuration simplifies the fabrication process and reduces costs compared to micromirror-based modulators. However, these modulators are limited in their optical efficiency and aperture. Here, we present a MEMS grating modulator with a notably extendable aperture and a high optical efficiency that benefits from the adoption of a tunable sinusoidal grating. Instead of end-constrained movable ribbons, we constrain the MEMS grating modulator through broadside-constrained continuous ribbons. The end-free grating enables improved scalability along the ribbons, and the continuous sinusoidal surface of the grating allows an increased fill factor. As an example, we experimentally demonstrate a MEMS grating modulator with a large-scale aperture of 30 × 30 mm and an optical efficiency of up to 90%. The modulation depth enables intensity modulation across a broad wavelength range from 635 to 1700 nm. The experimental results demonstrate that the reported modulator has a mechanical settling time of 1.1 μs and an extinction ratio of over 20 dB. Furthermore, it offers a dynamic modulation contrast of over 95% within a 250 kHz operating frequency and achieves full modulation within a field of view (FOV) of ±30°. The reported MEMS grating modulator holds promise for application in high-speed light attenuation and modulating retroreflector free-space optical (MRR-FSO) communication systems. Our device also paves new ways for future high-speed, energy-efficient, and cost-effective communication networks.